FLT3 ligand kinetic profile predicts response to treatment in patients with high-risk myelodysplastic syndrome / chronic myelomonocytic leukemia receiving CPX-351: a study from the Groupe Francophone des Myélodysplasies - Pierre Peterlin; Joëlle Gaschet; Pascal Turlure; Marie-Pierre Gourin; Pierre-Yves Dumas; Sylvain Thepot; Ana Berceanu; Sophie Park; Marie-Anne Hospital; Thomas Cluzeau; Jose-Miguel Torregrosa-Diaz; Louis Drevon; et al. (Haematologica)
Not available.